Analysis of narrow-band dispersive interdigital transducers by the scattering-matrix method for periodic metal strips - DANICKI, Eugeniusz (Archives of Acoustics, 1988)
A model of the interdigital transducer of surface acoustic wave (SAW) is introduced on the strength of the scattering matrix for a single metal strip of the periodic system deposited on a piezoelectric substrate surface. The model describes properties of the transducer within the wide frequency band and takes into account the SAW reflection of electrical origin from the metal strips. The calculations performed for narrow-band dispersive filters show that the SAW reflections from the transducer electrodes distort the filter response not only as a result of the immediate effect upon the filter frequency characteristic, but also through the frequency-dependent change in the transducer admittance. A presented method for analyzing inhomogeneous systems may have some other applications, e.g. in a theory of superlattice.